2022
DOI: 10.1182/bloodadvances.2021004934
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of IDH1/2 mutational subclasses on outcome in adult AML: results from a large multicenter study

Abstract: Mutations of the isocitrate dehydrogenase-1 (IDH1) and IDH2 genes are amongst the most frequent alterations in acute myeloid leukemia (AML) and can be found in ~20% of patients at diagnosis. Among 4930 patients (median age 56 years, interquartile range 45-66) with newly diagnosed, intensively treated AML, we have identified IDH1 mutations (mIDH1) in 423 (8.6%) and IDH2 mutations (mIDH2) in 575 (11.7%) patients. Overall, there were no differences in response rates or survival for patients with mIDH1 or mIDH2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Previous studies generated partly controversial results, either associating IDH mut with better outcome [ 8 , 13 ] and studies reporting a negative impact on outcome [ 2 , 14 , 16 ]. More recently, it was shown that IDH mutational subgroups associated with different biological features have different prognostic impact, suggesting to provide an explanation for inconsistent results concerning prognosis and survival so far [ 6 , 23 , 46 ]. To add a next level of complexity, different mutational IDH variants are associated with differential co-mutational patterns or karyotypes, incorporating prognostic value and even potentially defining distinct genomic categories in AML [ 10 , 15 , 23 , 46 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies generated partly controversial results, either associating IDH mut with better outcome [ 8 , 13 ] and studies reporting a negative impact on outcome [ 2 , 14 , 16 ]. More recently, it was shown that IDH mutational subgroups associated with different biological features have different prognostic impact, suggesting to provide an explanation for inconsistent results concerning prognosis and survival so far [ 6 , 23 , 46 ]. To add a next level of complexity, different mutational IDH variants are associated with differential co-mutational patterns or karyotypes, incorporating prognostic value and even potentially defining distinct genomic categories in AML [ 10 , 15 , 23 , 46 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, their prognostic and predictive relevance is not fully resolved and standard AML risk stratification does not yet include IDH1 or IDH2 mutations [ 4 ]. However, there is growing evidence that IDH mutations contribute both prognostic and predictive value [ 2 , 5 , 6 ]. There have been inconsistent results regarding outcome, including complete remission (CR) rate, relapse-free survival (RFS) and overall survival (OS) depending on IDH1 and IDH2 mutational status, respectively [ 2 , 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our data reinforce the notion that IDH1 / 2 mutational status does not impact on prognosis, in line with the reports by Di Nardo and Chotirat [ 17 , 18 ]. Accordingly, Middeke et al recently reported on the prognostic role of IDH1 / 2 mutations in the largest AML cohort treated with intensive chemotherapy [ 26 ]. They did not find any difference in response rates, nor in survival for patients carrying IDH1 / 2 mutations when compared to IDH1 / 2 -WT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that an IDH2 mutation is a marker for poor prognosis in patients with AML, and the overall survival (OS) time of the patients with wild-type IDH2 was greater than that of patients with an IDH2 mutation (45). However, another study found that patients with IDH2 R172K mutations have improved relapse-free survival (RFS) and OS times compared with patients with the wild-type (46). Therefore, this topic remains controversial, and more experimental data are needed to confirm which view is correct.…”
Section: Obstructed Hematopoietic Differentiation Caused By Idh2mentioning
confidence: 99%